2006
DOI: 10.1097/00042737-200604000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Biliary stenting alone versus biliary stenting plus sphincterotomy for the treatment of post-laparoscopic cholecystectomy biliary leaks: a prospective randomized study

Abstract: Endoscopic therapy of biliary leaks with a small-diameter biliary stent alone is as effective and safe as endoscopic sphincterotomy followed by insertion of a large-diameter stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 15 publications
3
44
0
2
Order By: Relevance
“…In particular, endoscopic treatment has proved to be very effective with type A lesions and success rates between 89 and 100% have been published [14,[25][26][27]. Our findings are consistent with the previous findings in this respect as 95% of these injuries could be treated endoscopically in the current patient population.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, endoscopic treatment has proved to be very effective with type A lesions and success rates between 89 and 100% have been published [14,[25][26][27]. Our findings are consistent with the previous findings in this respect as 95% of these injuries could be treated endoscopically in the current patient population.…”
Section: Discussionsupporting
confidence: 91%
“…Our study was not designed or powered to evaluate efficacy. However, the previously mentioned data comparing 7 Fr stent alone versus 10 Fr stent with sphincterotomy demonstrated similar efficacy [16]. Studies in animal models have shown biliary stent placement alone was found to be superior to sphincterotomy alone in controlling bile leaks after cholecystectomy [15].…”
Section: Discussionmentioning
confidence: 80%
“…In a recent randomized trial stent placement alone using 7 Fr stents were compared to 10 Fr stent placement with concomitant biliary sphincterotomy [16]. In the stent only group 1/28 patients (4%) developed mild pancreatitis compared to 2/28 patients (7%) (1 mild and 1 moderate) in the stent with sphincterotomy group.…”
Section: Discussionmentioning
confidence: 99%
“…15 Mavrogiannis et al showed that a 7F stent placement for cystic duct leak postcholecystectomy is as safe and effective as biliary stenting with sphincterotomy followed by a 10F large-diameter stent. 9,90 Luigiano et al used two fcSEMS for managing a complex bile leak after open cholecystectomy. 91 A 10 mm diameter, 8 cm long fully covered Wallflex stent was initially placed, but ERCP showed the proximal end below the bile duct, causing leaks.…”
Section: Management Of Biliary Leaksmentioning
confidence: 99%